Reversal Learning Phenotypes are Linked with Novel Genetic Loci in Diversity Outbred Mice - Bagley, Jared R; Bailey, Lauren S; Gagnon, Leona H; He, Hao; Philip, Vivek M; Reinholdt, Laura G; Tarantino, Lisa M; Chesler, Elissa J; Jentsch, James D (bioRxiv, 2022)
Impulsive behavior and impulsivity are heritable phenotypes that are strongly associated with risk for substance use disorders in human subjects. Consequently, identifying the neurogenetic mechanisms that influence impulsivity may also reveal novel biological insights into addiction vulnerability. Past studies from our laboratory using the BXD and Collaborative Cross (CC) recombinant inbred mouse panels have revealed that behavioral indicators of impulsivity measured in a reversal learning task are heritable and are genetically correlated with aspects of intravenous cocaine self-administration. Genome wide linkage studies in the BXD panel revealed a quantitative trait locus (QTL) on chromosome 10, but the specific genes affecting this trait remain elusive. To achieve greater precision in our mapping efforts, we have turned to Diversity Outbred (DO) mice. A total of 392 DO mice (230 males, 295 females) were successfully phenotyped using the same reversal learning test utilized in our earlier studies. Our primary indicator of impulsive responding, a measure that isolates the relative difficulty mice have with reaching performance criteria under reversal conditions, revealed a genome wide significant QTL on chromosome 7 (max LOD score = 8.73, p<0.05). A measure of premature responding akin to that implemented in the 5-choice serial reaction time task yielded a suggestive QTL on chromosome 17 (max LOD score = 9.14, p<0.1). Positional candidate genes were prioritized (2900076A07Rik, Wdr73 and Zscan2) based upon expression QTL data we collected in DO and CC mice and analyses using publicly available gene expression and phenotype databases. These findings may advance understanding of the genetics that drive impulsive behavior and enhance risk for substance use disorders. Competing Interest Statement The authors have declared no competing interest.